Anticoagulation management by community pharmacists in New Zealand: an evaluation of a collaborative model in primary care. (23rd September 2014) - Harrison, Jeff; Shaw, John P.; Harrison, Jenny E.
Abstract Objectives Despite the introduction of new oral anticoagulants, vitamin K antagonists remain the mainstay of the prevention and treatment of thromboembolism. The advent of affordable point‐of‐care testing presents an opportunity for community pharmacists to provide anticoagulation management services, better utilizing their training, reducing the workload on medical practices and improving accessibility and convenience for patients. This study aimed to determine the effectiveness of anticoagulation management by community pharmacists. Methods All patients enrolled in a pilot programme for a community pharmacy anticoagulation management service using point‐of‐care international normalized ratio testing and computer‐assisted dose adjustment were included in a follow‐up study, including before–after comparison. Outcomes included time in therapeutic range (TTR), time above and below range, number and proportion of results outside efficacy and safety thresholds, and a comparison of care led by pharmacists and care led by a primary‐care general practitioner (GP). Key findings A total of 693 patients were enrolled, predominantly males over 65 years of age with atrial fibrillation. The mean TTR was 78.6% (95% CI 49.3% to 100%). A subgroup analysis (n = 221) showed an increase in mean TTR from 61.8% under GP‐led care to 78.5% under pharmacist‐led care (P < 0.001), reflecting a reduction in the time above and, in particular, below the range. The mean TTR by pharmacy ranged from 71.4% to 84.1%. The median number of tests per month was not statistically different between GP‐ and pharmacist‐led care. Conclusions Community‐pharmacist‐led anticoagulation care utilizing point‐of‐care testing and computerized decision support is safe and effective, resulting in significant improvements in TTR. Our results support wider adoption of this model of collaborative care.